The Effect of Depth on Growth and Survival of Abalone Shells (Haliotis sp.) with A Multi-Level System - Mau'ud, Mohamad; Junaidi, Muhammad; Scabra, Andre Rahmat (Jurnal Biologi Tropis, 2024)
Abalone shells (Haliotis sp.), known as seven-eyed shellfish, are a type of gastropod. Abalone shells have high economic value accompanied by high market demand. The selling price of abalone reaches Rp. 250,000 (shells and meat). To optimize abalone cultivation activities with a long growth time, one method is needed for cultivating abalone shells in KJA (Floating Net Cages), namely using a tiered system in one hanger with different depths, namely 1m, 2m, 3m, 4m and 5m. so that it can increase land efficiency in cultivation activities. The aim of this research is to evaluate and analyze the effect of depth on the growth and survival rate of abalone shells (Haliotis sp.) using a multilevel system. The method used in this research was a Completely Randomized Design (CRD) experimental method with five treatments and three replications. The results of the research conducted showed that the results of the anova test on absolute length growth, specific length growth rate, absolute weight growth, specific weight growth rate, and survival of abalone shells (haliotis sp.) showed that they had no real influence (>0.05) on the maintenance of abalone shells. Based on the research results, it can be concluded that using a tiered system at different depths does not have a real effect on the growth of abalone shells because the water quality conditions at a depth of 1-5 meters are optimal so they can support the growth of abalone shells.